HUBUNGAN REGULASI EMOSI DENGAN SUBJECTIVE WELL BEING PADA REMAJA YANG TINGGAL DI PONDOK PESANTREN - Rita Wahyu Widiastuti; Widyastuti Widyastuti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Adolescents with high subjective well being will experience life satisfaction and experience joy more often, and rarely experience unpleasant emotions, such as sadness and anger. Adolescents with high subjective well being will tend to have emotions that are always positive which in the end all life problems and developmental tasks can be resolved properly. This study aims to determine the effect of the relationship between emotion regulation and subjective well being in adolescents who live in boarding schools. The variables of this study are emotion regulation as the independent variable (X) and subjective well being as the dependent variable (Y). This research design uses a correlational approach with a sample of 108 students, using probability sampling technique with simple random sampling type. This research instrument is the Satisfaction With Life Scale (SWLS) and Scale of Positive An Negative Experience (SPANE) with Cronbach's Alpha reliability of 0.877 to measure subjective well being. The Emotional Regulation Questionnaire (ERQ) with Cronbach's Alpha reliability of 0.730 to measure emotion regulation. Data analysis in this study used Pearson product moment correlation. The results of data analysis show that there is no significant relationship between emotion regulation and subjective well being in adolescents at boarding schools with a sig value. 0,383 (p<0,05).